Widespread ecomorphological convergence in multiple fish families spanning the marine–freshwater interface. Issue 1854 (17th May 2017) - Davis, Aaron M.; Betancur-R, Ricardo
Abstract : The theoretical definition and quantification of convergence is an increasingly topical focus in evolutionary research, with particular growing interest on study scales spanning deep phylogenetic divergences and broad geographical areas. While much progress has recently been made in understanding the role of convergence in driving terrestrial (e.g. anole lizards) and aquatic (e.g. cichlids) radiations, little is known about its macroevolutionary effects across environmental gradients. This study uses a suite of recently developed comparative approaches integrating diverse aspects of morphology, dietary data, habitat affiliation and phylogeny to assess convergence across several well-known tropical–temperate fish families in the percomorph suborder Terapontoidei, a clade with considerable phenotypic and ecological diversity radiating in both marine and freshwater environments. We demonstrate significant widespread convergence across many lineages occupying equivalent trophic niches, particularly feeding habits such as herbivory and biting of attached prey off hard substrates. These include several examples of convergent morphotypes evolving independently in marine and freshwater clades, separated by deep evolutionary divergences (tens of millions of years). The Terapontoidei present a new example of the macroevolutionary dynamics of morphological and ecological coevolution in relation to habitat and trophic preferences, at a greater phylogenetic and habitat scale than most well-studied adaptive radiations.